Multiplexed detection of pathogen-specific DNA using engineered zinc finger proteins without target amplification. Issue 37 (2nd September 2016) - Kim, Moon-Soo; Kim, Juhwa
Abstract : Direct chemiluminescence detection of double-stranded DNA specific for bacterial pathogens using engineered zinc finger proteins (ZFPs). Abstract : Multiplexed detection of pathogen-specific DNA sequences in a simple and reliable way is in great demand for clinical and biomedical applications. However, there is still a lack of available DNA detection methods that are simple and pathogen-selective for point-of-care (POC) testing. Here, we report a novel zinc finger protein (ZFP)-based chemiluminescence method for direct detection of pathogenic double-stranded DNA (dsDNA) in a multiplexed platform. ZFPs are custom-designed to identify unique pathogenic DNA sequences. ZFP-based chemiluminescence detection of dsDNA provides sufficient sensitivity (≤50 fmol) and high specificity without target DNA amplification. Our study addresses the potential of developing a simple and selective pathogen detection method in a multiplexed fashion needed for POC applications.